Determinación de la filiación en la procreación asistida - Varsi-Rospigliosi, Enrique (2017)
The unstoppable advance of the procreation overwhelms family law, especially in the filial issue. The prevalence of will is the current trend in the determination of the filial link, displacing the biogenetic aspect, tending to its debiologization. The determination of the affiliation, result of assisted reproduction techniques, is focus on volunteer parenthood as a legal event composed of volitional, social and affective elements; the genetic link is left to one side to give way to socio-affective paternity.